(untitled) (Research, Society and Development, 2021)
Objective: Women affected by endometriosis who carry the infertility factor have a decline in their personal and social lifestyle, caused by sadness and anguish. Thus, the aim of this study will be to analyze the psychological impacts and nursing care in women affected by endometriosis. Method: It consists of an integrative literature review, which allows considering the evaluation of the present bibliography, with the applicability of extensive themes, samples, studies that significantly emerge their results in practice. Results: Among the studies selected for the research, eight of the articles that were cited in the text were published in 6 different journals, from 2010 to 2021. Conclusion: It is concluded with this study that endometriosis is a disease that lodges itself and it causes numerous disorders in women’s quality of life. Thus, it is expected to contribute so that nursing care in the management of endometriosis may be seeking new knowledge regarding the treatment of this disease, considering the importance of practicing new research on the topic addressed.